HABITUS OF DEVICE USE AFTER ONLINE LEARNING AND ITS IMPACT ON ACADEMIC PERFORMANCE - Fadillah Rahmi Nasution; Hadriana Marhaeni Munthe; Linda Elida; T. Ilham Saladin; Henri Sitorus (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
The Covid-19 pandemic has brought changes to the world of education. Gadgets and the internet are effective media used during online learning. Students at SMA Negeri 1 Galang have become accustomed to using devices and various learning applications. Gadgets become something valuable and a necessity. The use of gadgets gives birth to new behaviors that are not present just like that. The habitus of using devices is getting stronger after online learning. The purpose of this study is to see the extent of the habitus of using devices after online learning for Class XII students of SMAN Negeri 1 Galang TP. 2023/2024. This research uses a qualitative approach with descriptive method. The results showed that the use of gadgets during online learning changed the informants' interaction patterns with technology. Habits in the use of gadgets have an influence on the lives of informants and form new habits. In addition, schools and families as arenas (fields) participate in shaping the habitus of using gadgets. Providing gadgets is done without planning and equipping students with strong digital literacy. Meanwhile, in power relations, students dominate teachers and parents in the use of devices. The use of devices after online learning supports students' social capital, making it easier to interact and build friendship networks. Gadgets also become symbolic capital for students, where the model, brand and price of gadgets become a reference for students to be said to be “cool”. Gadgets as cultural capital show that students who are able to use various applications and utilize gadgets for learning and positive things are considered smarter by their friends. Meanwhile, gadgets as economic capital show that students are able to utilize gadgets as a tool to earn money and transact online. After online learning, the habitus of using gadgets is more used for games, social media, shopping and online transactions than for learning activities